Analisa Kelayakan Investasi Sektor Pertanian Bali - Dian Novita Sari; Cokorda Gde Bayu Putra; Ni Komang Sumadi; Mirah Ayu Putri Trarintya (Jurnal Widya Akuntansi dan Keuangan, 2023)
The purpose of this study was to describe information on market analysis, cost analysis, and financial analysis of the investment potential and opportunities that are proposed in Tabanan Regency and produce a study document as material for investors in assessing the feasibility of investing in investment proposals in Tabanan Regency. The method used in this research is qualitative research with a case study approach. The data collection technique used in this study is through direct observation in the field. By analyzing the data that has been obtained, the results of this study are obtained, namely the investment proposal in Tabanan Regency with the planned Red Rice Restaurant project in Jatiluwih Village, Penebel District which is very interesting to develop and the calculation results from the data obtained show that the investment is feasible.